MYTHOLOGICAL TECHNIQUES OF MEANING FORMATION IN THE NOVEL “PETRII AND DOVBUSHCHUKY” BY IVAN FRANKO - Lutsak, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes the mythological techniques of meaning formation in the genre structure of the novel “Petrii and Dovbushchuky” by Ivan Franko. They caused such poetical features of this work, as indiscreteness of time-space, figurative and mental world, cyclicity and binarity of plot moves, syncreticity of genre and genus features and montagety of composite structure.